Blood pressure reduction in hypertensive acute ischemic stroke patients does not affect cerebral blood flow. Issue 9 (September 2019) - Kate, Mahesh; Asdaghi, Negar; Gioia, Laura C; Buck, Brian; Majumdar, Sumit R; Jeerakathil, Thomas; Shuaib, Ashfaq; Emery, Derek; Beaulieu, Christian; Butcher, Kenneth
The effect of blood pressure (BP) reduction on cerebral blood flow (CBF) in acute ischemic stroke is unknown. We measured regional CBF with perfusion-weighted MRI before and after BP treatment in a three-armed non-randomized prospective controlled trial. Treatment arm assignment was based on acute mean arterial pressure (MAP). Patients with (MAP) >120 mmHg ( n = 14) were treated with intravenous labetalol and sublingual (SL) nitroglycerin (labetalol group). Those with MAP 100–120 mmHg ( n = 17) were treated with SL nitroglycerin (0.3 mg) ('NTG Group') and those with baseline MAP<100 mmHg ( n = 18) were not treated with antihypertensive drugs (untreated group). Forty-nine patients (18 female, mean age 65.3 ± 12.9 years) were serially imaged. Labetalol reduced MAP by 12.5 (5.7–17.7) mmHg, p = 0.0002. MAP remained stable in the NTG (6.0 (0.4–16, p = 0.3) mmHg and untreated groups (−0.3 (−2.3–7.0, p = 0.2) mmHg. The volume of total hypoperfused tissue (CBF<18 ml/100 g/min) did not increase after labetalol (−1.1 ((−6.5)–(−0.2)) ml, p = 0.1), NTG (0 ((−1.5)–4.5) ml, p = 0.72), or no treatment 0.25 ((−10.1)–4.5) ml, p = 0.87). Antihypertensive therapy, based on presenting BP, in acute stroke patients was not associated with an increased volume of total hypoperfused tissue.